Dare to die : a death on demand mystery - Hart, Carolyn G. (New York : William Morrow, 2009)
A mysterious young woman returns to the island to make amends, but a ruthless killer fears she will recall one long ago, foggy night.
edited hb 2015-06-16
Keywords: Darling, Annie Laurance (Fictitious character) -- Fiction; Darling, Max (Fictitious character) -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction